O estado da arte dos estudos sobre os aspectos genéticos associados ao transtorno do espectro autista - Chaves, Rafael Borges (2019)
The objective of this study was to characterize and quantify published articles on genetic polymorphisms associated with Autistic Spectrum Disorder (ASD), through a scientometric analysis. A survey of the articles was done through the Scopus database using the keywords: "Autism * Spectrum Disorder and gene". In 17 years, 1040 articles published on genetic polymorphisms related to ASD. There was an increase in the number of these publications over time (p <0.0001). On average, the impact factor of the journals was 5.76 with 10.84 collaborators per article and cited 37.24 times. The impact factor tends to increase with the number of citations (p <0.0001) and with the number of collaborators (p = 0.0014). The number of citations tends to increase in studies with more employees (p <0.0001) and decrease in more recent articles (p <0.0001). Medicine was an area of knowledge that stood out in the publications and Brazil ranks 17th in the ranking of the countries that published the most on genetic polymorphisms related to ASD. A total of 717 TEA-related polymorphic genes were identified and of these 15 genes were studied in 30 or more articles. Therefore, it is noticed that the scientific community has shown interest in developing research related to genetic polymorphisms associated with ASD.